(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In this study the learning styles of higher secondary students of Kanniyakumari District in Tamil Nadu was focused. The main objectives of the study were to find out the level of learning styles of higher secondary students and to find out the significant difference in learning styles with regard to gender. 609 samples were selected by simple random sampling technique. Learning style inventory developed and validated by Maria Jeslin.M and Selvakumar.K.R (2022) was used to collect the data. Statistical techniques used in this study were percentage analysis and ‘t’-test to find out the significant difference in learning style with regard to gender. The results indicated that there was a significant difference in the learning styles of higher secondary students irrespective of their gender